Evaluation of the Incremental Prognostic Utility of Increasingly Complex Testing in Chronic Heart Failure. (July 2015) - Ahmad, Tariq; O'Brien, Emily C.; Schulte, Phillip J.; Stevens, Susanna R.; Fiuzat, Mona; Kitzman, Dalane W.; Adams, Kirkwood F.; Kraus, William E.; Piña, Ileana L.; Donahue, Mark P.; Zannad, Faiez; Whellan, David J.; et al.
<x xml:space="preserve">Abstract</x> Background— Current heart failure (HF) risk prediction models do not consider how individual patient assessments occur in incremental steps; furthermore, each additional diagnostic evaluation may add cost, complexity, and potential morbidity. Methods and Results— Using a cohort of well-treated ambulatory HF patients with reduced ejection fraction who had complete clinical, laboratory, health-related quality of life, imaging, and exercise testing data, we estimated incremental prognostic information provided by 5 assessment categories, performing an additional analysis on those with available N-terminal pro–B-type natriuretic peptide (NT-proBNP) levels. We compared the incremental value of each additional assessment (quality of life screen, laboratory testing, echocardiography, and exercise testing) to baseline clinical assessment for predicting clinical outcomes (all-cause mortality, all-cause mortality/hospitalization, and cardiovascular death/HF hospitalizations), gauging incremental improvements in prognostic ability with more information using area under the curve and reclassification improvement (net reclassification index), with and without NT-proBNP availability. Of 2331 participants, 1631 patients had complete clinical data; of these, 1023 had baseline NT-proBNP. For prediction of all-cause mortality, models with incremental assessments sans NT-proBNP showed improvements in C-indices (0.72 [clinical model alone]−0.77 [complete model]). Compared with baseline clinical assessment alone, net reclassification index improved from 0.035 (w/laboratory data) to 0.085 (complete model). These improvements were significantly attenuated for models in the subset with measured NT-proBNP data (c-indices: 0.80 [w/laboratory data]−0.81 [full model]); net reclassification index improvements were similarly marginal (0.091→0.096); prediction of other clinical outcomes had similar findings. Conclusions— In chronic HF patients with reduced ejection fraction, the marginal benefit of complex prognostic evaluations should be weighed against potential patient discomfort and cost escalation. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifier: NCT00047437.